186k views
3 votes
ANY ONE PLZ HELP 25 POINTS PROVE THAT x³+y³+z³-3xyz=(x+y+z)(x+ωy+ω²z)(x+ω²y+ωz)

User Linkas
by
5.2k points

1 Answer

4 votes

Answer:

Proved

Explanation:

Taking R.H.S

=>
(x+y+z)[x(x+w^2y+wz)+wy(x+w^2y+wz)+w^2z(x+w^2y+wz)]

=>
(x+y+z)(x^2+w^2xy+wxz+wxy+w^3y^2+w^2yz+w^2xz+w^4yz+w^3z^2)

Remember ∴ ω³ = 1

So we'll replace all ω³'s with 1

=>
(x+y+z)(x^2+y^2+z^2+w^2xy+wxy+w^2yz+w^4yz+w^2xz+wxz)

=>
(x+y+z)[x^2+y^2+z^2+xy(w^2+x)+w^2yz+w^3*wyz+xz(w^2+w)]

Remember ∴ ω²+ω = -1

=>
(x+y+z)[x^2+y^2+z^2+xy(-1)+yz(w^2+w)+xz(-1)]

=>
(x+y+z)(x^2+y^2+z^2-xy-yz-xz)

According to formula:

x³+y³+z³-3xyz =
(x+y+z)(x^2+y^2+z^2-xy-yz-xz)

So, it becomes

=>
x^3+y^3+z^3-3xyz

User BasZero
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.